Biodiesel production from waste cooking oil using a novel biocatalyst of lipase enzyme immobilized magnetic nanocomposite. (1st April 2022) - Parandi, Ehsan; Safaripour, Maryam; Abdellattif, Magda H.; Saidi, Majid; Bozorgian, Alireza; Rashidi Nodeh, Hamid; Rezania, Shahabaldin
Highlights: The new heterogeneous nanocatalyst was used for conversion of WCO to biodiesel. Candida Antarctica Lipase B was immobilized on a magnetic hybrid sol-gel nanocomposite. The biodiesel yield was 96% at a temperature of 40 °C, molar ratio of 4:1, contact time of 30 h, and catalyst dosage of 1 g. FAMEs yield decreased from 91% to 70% after six cycles. Abstract: The main objective of the present study was to produce biodiesel from waste cooking oil (WCO) in the presence of Candida Antarctica Lipase B (CALB), which was immobilized on a magnetic hybrid sol-gel nanocomposite. For this purpose, the Fe3 O4 magnetic nanoparticles synthesized by the co-precipitation technique and were coated with silica (SiO2 ) and then functionalized with organic-inorganic hybrid tetraethyl orthosilicate (TEOS) and N-[3-(trimethoxysilyl)propyl] ethylenediamine (TSD). Subsequently, the synthesized and modified magnetic nanoparticle was characterized by using X-ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), Vibrating-Sample Magnetometer (VSM), Scanning Electron Microscope (SEM), and Energy Dispersive Spectroscopy (EDS). The optimized condition of the lipase immobilization was in lipase concentration of 2.5 mg mL −1, immobilization time of 5 h, immobilization temperature of 35 °C, and pH of 7. The thermal stability of the immobilized lipase was greatly increased compared to the free enzyme. The effect of operating parameters including reaction temperature (30–70 °C), methanol/oil (M/O) molar ratio (1:1–5:1), contact time (12–36 h), and catalyst dosage (0.2–1 g) was evaluated in terms of biodiesel production yield. Based on the results, the maximum yield of biodiesel using the synthesized biocatalyst was 96%, at a temperature of 40 °C, M/O molar ratio of 4:1, contact time of 30 h, and catalyst dosage of 1 g. The obtained results indicated that the synthesized biocatalyst can be used as an efficient heterogeneous catalyst for biodiesel production in accordance with the fuel standard (ASTM D6751).